The Role of Islamic Religious Education Curriculum in Developing Students’ Religious Values - Fauziah Risa Rabbani; Muhammad Fathur Ramadan; Amirah Arifah (Jurnal Pendidikan Islam, 2024)
Islamic religious education in Indonesia plays an important role in shaping the character and morals of the younger generation. The Islamic religious education curriculum not only teaches religious knowledge, but also aims to form students who are able to practice Islamic values in their daily lives. This article explores the role of curriculum in the development of Islamic religious education values in madrasah and Integrated Islamic Schools (SIT). Through a literature study and descriptive qualitative research method, this study investigates how the concept of tarbiyah, i.e. comprehensive education and character building, is integrated in the Islamic religious education curriculum. Primary data was obtained through interviews and observations with participants from madrasahs. The results show that despite challenges in its implementation, such as adaptation to contemporary Islamic values and adjustment to students' learning styles, the curriculum succeeds in shaping students' characters with integrity and commitment to religious values. This article contributes to understanding the importance of Islamic religious education in shaping a young generation that is ready to face the challenges of the times by holding fast to religious values.